ANALISIS PENGELOLAAN KEUANGAN DANA DESA - Djauhar, Asri; Manan, La Ode Abd.; Awit, Daswin (Sultra Journal of Economic and Business, 2020)
This study aims to determine the Village Fund Management in Togomangura Village. To achieve these objectives, qualitative research methods are used to decipher data descriptively. Data collection techniques are done by observation, interviews, and documents and archives using qualitative descriptive analysis techniques. The results showed: 1). For the stages of village financial planning in Togomangura Village, the Togomangura village government has managed the village fund finances in accordance with Permendagri Number 113 of 2014 concerning Village Fund Financial Management. 2). For the Village Fund budgeting phase in Togomangura Village, it has been carried out in accordance with existing principles, namely by budgeting village funds in accordance with the RKP of the Village that was determined at the planning stage and in accordance with Permendagri Number 113 of 2014 concerning Village Financial Management. 3). The implementation of Village Fund Financial Management in Togomangura Village has been very good and in accordance with applicable regulations namely Permendagri No. 113 of 2014 concerning the implementation of village finances and the PDTT Permendes Number 19 of 2017 concerning Priorities for the Use of Village Funds in 2018. 4). The administration of the Village Fund Financial Management Program in Togomangura Village is already good, because it is in accordance with applicable regulations namely Permendagri No. 113 of 2014 concerning the implementation of village finance. 5). Village Fund Financial Reporting in Togomangura Village is not in accordance with Permendagri No. 113 of 2014 concerning village financial management. This is evidenced by the late TPK Field and Village Treasurers in submitting reports. 6). Monitoring of Village Funds by the BPD, it can be concluded that the BPD in carrying out its functions runs well but is less than optimal. This is because there are several factors that create obstacles, namely Human Resources (HR) so that the awareness of BPD members is less than optimal in carrying out their duties and functions. 7). The use of Village Funds in Togomangura Village in 2018 is not in accordance with the priority of use according to the PDTT Regulation No. 19 of 2017 concerning the priority of using Village Funds in 2018. 8). Inhibiting factors in the management of the Village Fund in Togomangura Village, namely: Human Resources, Late Reporting, Internet Networks, Community Understanding, Poor Coordination.